GJMPBU 2021
DOI: 10.25259/gjmpbu_4_2021
|View full text |Cite
|
Sign up to set email alerts
|

The double trouble: COVID-19 associated mucormycosis a focused review and future perspectives

Abstract: Mucormycosis, a deadly fungal infection, has affected thousands of COVID-19 patients in India. Mucormycosis, formerly known as zygomycosis, is caused by the many fungi that belong to the family “Mucorales.” These molds are commonly found in soil, air, and damp walls and frequently colonize oral mucosa, nose, paranasal sinuses, and throat. The pathophysiological consequences of diabetes combined with the acute inflammatory surge in COVID-19 and steroid treatment weakens person’s immunity and renders susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Agnihotri, et al reported that a significant increase in the COVID-19 associated mucormycosis cases is strongly associated with treatment of corticosteroid in the diabetic patients treated for COVID-19. This finding is congruent to our study where 72.2% patients received steroids as a part of treatment for Covid-19 infection during hospitalization [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Agnihotri, et al reported that a significant increase in the COVID-19 associated mucormycosis cases is strongly associated with treatment of corticosteroid in the diabetic patients treated for COVID-19. This finding is congruent to our study where 72.2% patients received steroids as a part of treatment for Covid-19 infection during hospitalization [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…To cause such an aggressive and lethal infection, the causative mucormycosis fungi take advantage of the many alterations that SARS-CoV-2 infection generates on the host, such as ( Figure 1 ): Hyperglycemia, caused by the use of corticosteroids to treat COVID-19 [ 143 ] and dysregulation of the host receptor ACE2 (angiotensin-converting enzyme 2) observed during the viral infection [ 144 , 145 ] (explained in vii). Pre-existing diabetes is the main risk factor in most CAM cases [ 12 ] and is also related to an increase in the severity of SARS-CoV-2 infection [ 146 ]; Low pH, caused by diabetic ketoacidosis or metabolic acidosis caused by corticosteroid use [ 147 ], which reduces the leukocytes’ phagocytic activity and impairs bronchoalveolar macrophages migration and functions [ 12 , 148 ]; Immunosuppression, caused by SARS-CoV-2 infection and hypoxia, corticosteroids, and tocilizumab use [ 148 , 149 ] or patients’ previous comorbidities.…”
Section: Covid-19-associated Mucormycosismentioning
confidence: 99%
“…Therapeutic intervention with lactoferrin has been suggested to revert iron availability [ 157 , 158 , 159 ]; Pulmonary changes, including vascular endothielitis, thrombosis, and angiogenesis, caused by SARS-CoV-2 infection, which provides a focal point for fungal growth and dissemination [ 103 , 160 ]. The damage to alveolar cells can also promote anaerobic glycolysis, which causes lactic acidosis [ 145 ]; Overexpression of endothelial cells GRP-78, caused by hyperglycemia, acidosis, and iron availability, which enables angioinvasion, hematogenous dissemination, and tissue necrosis [ 58 ]; Dysregulation of ACE2 by SARS-CoV-2. By being present in many organs and tissues, the alteration of the receptor ACE2 expression causes a suitable environment for the development of mucormycosis.…”
Section: Covid-19-associated Mucormycosismentioning
confidence: 99%
See 2 more Smart Citations